Research Progress on Nano-Confinement Effects in Unconventional Oil and Gas Energy—With a Major Focus on Shale Reservoirs - Guo Wang; Rui Shen; Shengchun Xiong; Yuhao Mei; Qinghao Dong; Shasha Chu; Heying Su; Xuewei Liu (Energies)
Compared to conventional reservoirs, the abundant nanopores developed in unconventional oil and gas reservoirs influence fluid properties, with nano-confinement effects. The phase behavior, flow characteristics, and solid–liquid interactions of fluids are different from those in conventional reservoirs. This review investigates the physical experiments, numerical simulations, and theoretical calculation methods used in the study of nano-confinement effects in unconventional oil and gas energy. The impact of different methods used in the analysis of fluid phase behavior and movement in nanopores is analyzed. Nanofluidic, Monte Carlo method, and modified equation of state are commonly used to study changes in fluid phase behavior. Nano-confinement effects become significant when pore sizes are below 10 nm, generally leading to a reduction in the fluid’s critical parameters. The molecular dynamic simulation, Monte Carlo, and lattice Boltzmann methods are commonly used to study fluid movement. The diffusion rate of fluids decreases as nanopore confinement increases, and the permeability of nanoscale pores is not only an inherent property of the rock but is also influenced by pressure and fluid–solid interactions. In the future, it will be essential to combine various research methods, achieve progress in small-scale experimental analysis and multiscale simulation.